Human Neural Stem Cell Transplantation-Mediated Alteration of Microglial/Macrophage Phenotypes after Traumatic Brain Injury. Issue 10 (October 2016) - Gao, Junling; Grill, Raymond J.; Dunn, Tiffany J.; Bedi, Supinder; Labastida, Javier Allende; Hetz, Robert A.; Xue, Hasen; Thonhoff, Jason R.; DeWitt, Douglas S.; Prough, Donald S.; Cox, Charles S.; Wu, Ping
Neural stem cells (NSCs) promote recovery from brain trauma, but neuronal replacement is unlikely the sole underlying mechanism. We hypothesize that grafted NSCs enhance neural repair at least partially through modulating the host immune response after traumatic brain injury (TBI). C57BL/6 mice were intracerebrally injected with primed human NSCs (hNSCs) or vehicle 24 h after a severe controlled cortical impact injury. Six days after transplantation, brain tissues were collected for Western blot and immunohistochemical analyses. Observations included indicators of microglia/macrophage activation, M1 and M2 phenotypes, axonal injury detected by amyloid precursor protein (APP), lesion size, and the fate of grafted hNSCs. Animals receiving hNSC transplantation did not show significant decreases of brain lesion volumes compared to transplantation procedures with vehicle alone, but did show significantly reduced injury-dependent accumulation of APP. Furthermore, intracerebral transplantation of hNSCs reduced microglial activation as shown by a diminished intensity of Iba1 immunostaining and a transition of microglia/macrophages toward the M2 anti-inflammatory phenotype. The latter was represented by an increase in the brain M2/M1 ratio and increases of M2 microglial proteins. These phenotypic switches were accompanied by the increased expression of anti-inflammatory interleukin-4 receptor α and decreased proinflammatory interferon-γ receptor β. Finally, grafted hNSCs mainly differentiated into neurons and were phagocytized by either M1 or M2 microglia/macrophages. Thus, intracerebral transplantation of primed hNSCs efficiently leads host microglia/macrophages toward an anti-inflammatory phenotype that presumably contributes to stem cell-mediated neuroprotective effects after severe TBI in mice.